A Book Industry in Transition: The Shortage of Books in Indonesia in the Late 1940s and 1950s’ - Eline Sophie Kortekaas (Lembaran Sejarah, 2021)
This paper examines the book shortage crisis in Indonesia in the late 1940s and 1950s. After the Second World War, several Dutch colonial publishing houses decided to continue their businesses in Indonesia. During the second half of the 1940s there seemed to be an evergrowing demand for books in Indonesia, and by the end of 1949, several Dutch newspapers reported a so-called book crisis. A small booklet entitled De boekennood van modern Indonesië (Book Crisis of Modern Indonesia) (1949) seemed to be the herald of this alarming news. It was written by A.P. van Schieveen, who was a board member of the Vereniging van Indische Boekhandelaren, a society of Dutch book traders which had been established in 1926. In this booklet he emphasizes the importance of reading for Indonesia’s development, but also warns the Dutch publishing industry of the fact that the preferred second language seems to have become English. As a solution to support the continuing use of the Dutch language, he urged the Dutch publishing industry to distribute large quantities of Dutch books all over Indonesia. G. Ockeloen, the editor of Madjallah perdagangan buku di Indonesia/Maandblad voor de boekhandel in Indonesië (1949), responded to this matter. According to Ockeloen, Van Schieveen was stating the obvious, and he wrote that there was an even larger crisis going on, which was the shortage of books in Bahasa Indonesia.